The aerodynamic performance of a range of FIFA-approved footballs - Passmore, M.; Rogers, D.; Tuplin, S.; Harland, A.; Lucas, T.; Holmes, C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2012)
Much discussion surrounds the flight of a football, especially that which is perceived as irregular, and is typically done so with little understanding of the aerodynamic effects or substantive evidence of the path taken. This work establishes that for a range of FIFA-approved balls there is a significant variation in aerodynamic performance.